Analisa Karakteristik Kecelakaan Lalulintas Berbasis Gender di Kabupaten Magetan - I Made Kariyana (Syntax Corporation Indonesia, 2024)
Magetan Regency is one of the most remote districts in East Java Province, with a population that increases every year. This causes an increase in transportation needs. The dominant mode of transportation used in Magetan Regency is motorbikes, with the number of motorbikes in 2020 amounting to 317,085 (BPS Magetan Regency, 2023). The increase in the amount of transportation is accompanied by the risk of the transportation itself, namely traffic accidents. The number of traffic accidents in Magetan Regency in 2017 was 547 incidents; in 2018 it increased to 870 incidents. Based on previous research in the Magetan Regency area and its surroundings, it was found that accidents were influenced by human factors. Because of this, this research carried out an analysis of gender-based accident characteristics in Magetan Regency. Based on the results of the analysis using the descriptive analysis method using the cross-tabulation method in IBM SPSS, the driver characteristics were obtained, namely that the age of accident victims was predominantly 17-25 years old, and the majority of drivers had a driving license (SIM). The characteristics of accidents are that accidents are dominated by victims with minor injuries, occur in public places, and on weekdays.